Fruit Sorting System for Oranges Based on Size and Color Using Fuzzy Logic - Ali Rizal Chaidir; Panji Eka Prasetya; Arizal Mujibtamala Nanda Imron; Immawan Wicaksono; Guido Dias Kalandro; Gramandha Wega Intyanto (Journal of Educational Engineering and Environment, 2024)
Along with advances in technology, the use of human labor in managing agricultural products is decreasing because it has been replaced by robots. Robots perform better than human workers who have emotions and need time to rest. This can cause errors when sorting fruit due to lack of concentration caused by fatigue. The large harvest of oranges takes a long time to sort them, starting from color, size, weight, and price, before they are marketed. To make it easier for farmers to sort their harvest from orange fruit, this research was created titled "Citrus Fruit Sorting System Based on Size and Color Based on Fuzzy Logic." The sorting system based on color and size that will be made has the advantage that the fruit being sorted is more varied because it is equipped with fuzzy logic. Fuzzy logic allows membership values between 0 and 1, levels of gray as well as black and white, and in linguistic form, uncertain concepts such as "a little," "fairly," and "very." Apart from that, the system is made more human-friendly because the rule base is created by humans. The sorting tool that was made to be controlled using an Arduino UNO board with the help of Arduino IDE software managed to obtain a success rate of 62.5% for the low and medium-quality classes and a success rate of 87.5% for the high-quality class with an overall average success rate of 70.8 %.